국내 간호관리학 교육의 현황 및 고찰 - 김은경(Eun Kyung Kim); 김세영(Se Young Kim); 정면숙(Myun Sook Jung); 장금성(Keum Seong Jang); 김진현(Jinhyun Kim); 김종경(Jong Kyung Kim); 김영미(Young Mee Kim); 박은준(Eun Jun Park); 김기경(Ki Kyong Kim); 이해정(Hae Jung Lee) (Kanho Haengjŏng Hakhoe chi = The journal of Korean Nursing Administration Academic Society, 2011)
Purpose: The purpose of this study was to explore the current status of education for nursing management in Korea. Methods: A descriptive study was done using a questionnaire developed by the investigators. The data were collected by survey from 96 out of 129 nursing schools, between December 2010 and February 2011. Results: For 22.9% of nursing schools, there was no faculty for nursing management. The credits and subjects included in nursing management varied among the nursing schools. Lectures in subjects related to nursing management were given not only by nursing management faculty but also by faculty with other majors. There were more faculty and credits for nursing management courses in 4-year nursing schools than in 3-year schools. Conclusion: To improve the quality of education in nursing management, there is a need to standardized courses and provide nursing faculty who have majored in nursing management.